2008
DOI: 10.1002/ccd.21775
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of Biolimus A9 after elution from the Nobori stent in patients with coronary artery disease: The NOBORI PK study

Abstract: Objectives-The aim of this study was to assess the pharmacokinetics and tolerability of Biolimus A9 eluted from Nobori coronary stents.Background-The release kinetics and pharmacokinetics of drugs delivered via coronary stents have been shown to play an essential role in the efficacy and safety of drug eluting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…10 Biolimus A9 is eluted in a 2-phase process: the first phase is a burst release (≈40%) immediately after stent deployment, followed by sustained drug release and polymer degradation over a period of 6-9 months. 28 The potential advantages of the Nobori BES are mainly related to the biodegradable polymer, which should decrease the risk of late and very late events (especially ST) and, in turn, the need for prolonged dual antiplatelet therapy and the risk of long-term bleeding events after PCI. 29 However, despite any potential advantage of biodegradable polymer DES not emerging until the late follow-up period after polymer dissolution, it should be mandatory to demonstrate at least an equivalent efficacy and safety profile of the Nobori BES to currently approved DES at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…10 Biolimus A9 is eluted in a 2-phase process: the first phase is a burst release (≈40%) immediately after stent deployment, followed by sustained drug release and polymer degradation over a period of 6-9 months. 28 The potential advantages of the Nobori BES are mainly related to the biodegradable polymer, which should decrease the risk of late and very late events (especially ST) and, in turn, the need for prolonged dual antiplatelet therapy and the risk of long-term bleeding events after PCI. 29 However, despite any potential advantage of biodegradable polymer DES not emerging until the late follow-up period after polymer dissolution, it should be mandatory to demonstrate at least an equivalent efficacy and safety profile of the Nobori BES to currently approved DES at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Third-generation biolimuseluting stent was designed with a biodegradable polymer. 16 In large randomized trials, the biolimus-eluting stent has shown noninferiority after 1 year to the first-generation sirolimuseluting cypher stent 15 and the second-generation everolimuseluting Xience stent, 14 whereas long-term outcome favored the biolimus-eluting stent. 15 However, in the Scandinavian Organization for Randomized Trials With Clinical Outcome (SORT OUT) V trial, 17 comparing the biolimus-eluting Nobori stent and the sirolimus-eluting Cypher stent, the biolimuseluting stent failed to show noninferiority within 12 months.…”
Section: Sirolimus-eluting Vs Biolimus-eluting Biodegradable Polymer mentioning
confidence: 99%
“…The biodegradable polylactic acid polymer (PLLA and poly d,l-lactide-co-glycolide) is applied to the abluminal surface and metabolized within 6 to 9 months. 16 The stent elutes biolimus (15.6 μg/mm 2 ), for ≤30 days. Stents were implanted according to standard techniques.…”
Section: Study Stent Procedures and Antithrombotic Therapymentioning
confidence: 99%
“…Thus, BA9 easily crosses the cell membrane to achieve therapeutic effects in its target tissue and, compared with sirolimus-eluting Cypher stent (SES), leads to relatively low systemic exposure. 10 Third, the drug coating is asymmetrical on the abluminal surface of the stent, allowing the drug release to be directed almost entirely into the vessel wall for treatment of injured smooth muscle cells. Therefore, the textured surface is made only on the outside of stent.…”
Section: Design Of Biofreedom Stentmentioning
confidence: 99%